The influence of the perinatal environment on the heart: morphological, electrocardiographic, and multimodality imaging features - Giuseppe Mercuro; Pier Paolo Bassareo (Hygeia Press di Corridori Marinella, 2015)
The purpose of this paper is to review the studies performed to evaluate the influence of perinatal environment on neonatal heart, detected by electrocardiography, echocardiography, and other imaging techniques. Prenatal conditions (such as intrauterine growth retardation and prematurity at birth) and some post-natal events (such as perinatal asphyxia and corticosteroids administration), may have early and late detrimental effects on the heart may predispose to a number of future cardiovascular adverse events. For example, subjects born preterm may be at potentially higher risk of developing malignant ventricular arrhythmias as well. Moreover, in individuals born with an extremely low birthweight atrial septal aneurysms are present in about one third of the subjects in the study. Thus, a long-life follow up is suggested in these subjects. Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)